Compsodactylus, a new South American genus with one new species and two new combinations (Coleoptera: Scarabaeidae: Melolonthinae) - Fuhrmann, Juares (Zootaxa, 2012)
Compsodactylus new genus and C. scabrosus new species are described and C. martinezi (Frey, 1972) new combination and C. parvulus (Frey, 1970) new combination are redescribed and transferred from Dicrania LePeletier & Audinet-Serville, 1828. The new genus is placed in Macrodactylini (Coleoptera: Scarabaeidae: Melolonthinae) and occurs in the South American Andean and Preandean regions. A key to the species, modification on the recent generic key to Macrodactylini, and distributional map are presented.